Influence of genetic and aquired factors that modify serum bilirubin levels in the portuguese population - Rodrigues, Carina (2010)
The isoenzyme UDP-glucuronosyltransferase 1A1 (UGT1A1) catalyzes bilirubin glucuronidation by converting bilirubin in water-soluble glucuronides that then undergo biliary or renal elimination. During the last years, molecular studies have suggested that the presence of two extra bases in the repetitive promoter TATA box region of the UGT1A1 gene, described as (TA)7 allele, is responsible for the reduced UGT1A1 activity leading to hyperbilirubinemia. Gilbert’s syndrome (GS) is a genetic recessive disorder characterized by a mild unconjugated hyperbilirubinemia occurring in the absence of haemolysis or other evidence of liver disease. Patients with GS are often homozygous for the TA duplication. Several studies establish that unconjugated hyperbilirubinemia exhibits a mode of inheritance where a “major” recessive gene (UGT1A1) accounts for only a part of the serum bilirubin concentration. Recently, it was described that increased red cell mass probably plays a role in the pathogenesis of GS. Objective: Our study aims to determine the influence of the TA polymorphism, the presence of some environmental factors and increased red cell mass in serum bilirubin levels variation in Portuguese population. Material and Methods: We include in this study we recruit 165 young adults with average age (19.5 ± 2.1 years). All volunteers give their written informed consent and standardized interviewer-administered questionnaire was performed that included questions about smoking habits, oral contraceptive therapy, caloric intake, fasting time and physical activity. Exclusion criteria included the presence of liver and/or hematological disorders. After an overnight fasting, venous blood samples were collected in order to determine total and direct-reacting bilirubin, blood cell count and surrogate markers and isolate genomic DNA to perform the molecular study of UGT1A1 promoter region. Results: For the UGT1A1 genotyping we identified 15 homozygous individuals for (TA7/TA7), 79 heterozygous (TA6/TA7) and 71 were homozygous for the normal allele (TA6/TA6). Estimated frequency of (TA) was 33%, close to the 38,7% described for caucasians. A trend to higher bilirubin levels, without statistical significance, was found in males than in females, in non-smoking subjects and in female subjects that were under oral contraceptive therapy. Statistically significant correlations were found between bilirubin serum levels and fasting time (p=0.001) and caloric intake (p=0.03). No significant association was found between serum bilirrubin levels and physical activity. Our results strongly suggest that genetic background plays a major role in serum bilirubin levels variation but caloric intake, fasting time and red blood cell mass also contribute to this inter-individual variation. Conclusions: Our results strongly suggest that genetic background plays a major role in serum bilirubin levels variation but red blood mass and fasting time contribute to this inter-individual variation.